Optimized Projection and Fisher Discriminative Dictionary Learning for EEG Emotion Recognition - Gu, Xiaoqing; Fan, Yiqing; Zhou, Jie; Zhu, Jiaqun (Frontiers in Psychology, 2021)
EEG emotion recognition has drawn increasing attention in the brain computer interface (BCI) due to its great potentials in human-machine interaction applications. According to the characteristics of rhythms, EEG signals usually can be divided into several different frequency bands. Most existing methods concatenate multiple frequency band features together and treat them as a single feature vector. However, it is often difficult to utilize the band-specific information in this way. In this paper, an optimized projection and Fisher discriminative dictionary learning (OPFDDL) model is proposed to efficiently exploit the specific discriminative information of each frequency band. Using subspace projection technology, EEG signals of all frequency bands are projected into a subspace. The shared dictionary is learned in the projection subspace such that the specific discriminative information of each frequency band can be utilized efficiently, and simultaneously the shared discriminative information among multiple bands can be preserved. In particular, the Fisher discrimination criterion is imposed on the atoms to minimize within-class sparse reconstruction error and maximize between-class sparse reconstruction error. Then an alternating optimization algorithm is developed to obtain the optimal solution for the projection matrix and the dictionary. Experimental results on two EEG emotion recognition datasets show that our model can achieve remarkable results and demonstrate its effectiveness.